Penerapan Mobilisasi Dini terhadap Penurunan Intensitas Nyeri pada Ibu Post Sectio Caesarea - Aisyah Nilam Cahyani; Maryatun Maryatun (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Sectio Caesarea is considered very risky to be carried out by mothers who are about to give birth, due to the method that requires opening the wall or in medical terms Trans Abdominal Uterine Incision with pain that will be felt by a mother, which is a stressor that will be felt by the mother biologically which is felt physically. psychological and physical. The non-pharmacological techniques that can be used to reduce postoperative pain is early mobilization techniques. Early mobilization techniques are effective in reducing pain through several mechanisms, including eliminating the patient's concentration at the location of the pain in the operating area, reducing the activity of chemical mediators in the inflammatory process which increases the pain response. and minimize pain nerve transmission to the central nervous system. This research aims to know the results of implementationEarly Mobilization of Reducing Pain Intensity in Post Sectio Caesarea Mothers. This study used a quasi-experimental design with the pretest-posttest Nonequivalent Control Group design methodwithcase study descriptive method to 2 respondentsPost Sectio Caesarea. Based on the results of the implementation that has been done there is a decrease in pain intensity in patientspost sectio caesarea after being given the application of early mobilization.